The extent of Using Smart Phones In Obtaining Information among Students of Libraries Department at the University of Tishreen - عمران, ينل (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aims to identify the extent of Using Smart Phones In Obtaining Information among Students of Libraries Departmentat the University of Tishreen. The researcher has followed the descriptive design to collect the required information by using information sheet that distributed on students of the fourth year of the above mentioned departments, which was 70 students of both sex and only 65 of them have responded. The collected data has been analyzed via SPSS statistical program. Research findings showed that the smart phones are effective means to download information, and the majority of students have faith in them to download information. The researcher recommends to include the mobile phones gradually within the teaching process, together with the necessity of making the library services via Central Library's website of Tishreen University, over the mobile phones accessible.